La violación del Artículo 76 numeral 7 literal k de nuestra Carta Magna ante la aplicación de la Justicia Indígena en la comunidad de Sixipamba. - Chariguaman Manobanda, Tanya Isabel (2023)
The practice of indigenous law is aimed at the conservation of ancestral customs and traditions, originated within the territory of indigenous communities, since; The Constitution of the Republic of Ecuador in article 171 guarantees and/or recognizes the rights of indigenous peoples and nationalities. However, the decisions that have been made within the community, regarding the jurisdictional decisions that sanction internal problems in their territories, have caused conflicts and violation of constitutional rights because the indigenous authorities must have prior knowledge of the cases that they can and cannot be resolved within their territories. Reason why this research has as its main objective to know, guide, motivate respect for rights and life, their traditions, customs, their competence before the application of indigenous justice, with the aim of a harmonious coexistence within the Community of Sixipamba, since it has been observed in the cases that have been resolved, there is a violation of article 76 numeral 7 literal k of the Constitution of Ecuador. Based on the application of a methodology based on a quantitative research approach using as a data collection technique the survey of indigenous authorities belonging to a community and its inhabitants, in the collection of information it will be announced what types of cases have been resolved by a different community where the infraction was committed. In the same way, within the methodology, virtual platforms are used; where doctrine, jurisprudence and laws will be investigated in relation to the topic raised. The result that is intended to be obtained with the present investigation; is that the indigenous authorities administer indigenous justice in the community of Sixipamba, in accordance with constitutional norms without violating rights and guarantees.